Programas de intervenção precoce: caracterização e análise das pesquisas no contexto brasileiro - Candido, Ana Regina Lucato Sigolo (2017)
This research encompass two studies. The objectives of Study A composed by two steps: Stage 1- In the period of 10 years (2005 – 2014), identify and analyze theses and dissertations produced in Brazilian graduate program with objective of development proposal of Early Intervention Programs for children's development were identified and analyzed to seek main variables studied; and Stage 2: - The proposals of Early Intervention Programs developed that identified in previous stage were characterized and assessed. The Study B described evaluations of Early Intervention Programs after the event of researchers responsible for proposal and execution, as well as continuity of work after conclusion of research. The Study A based on data from the Theses and Dissertations Bank of Brazilian Digital Library (BDTD), whose search descriptors were: early attention, early stimulation, essential stimulation, child stimulation, child development stimulation, early intervention, development surveillance and screening of development. According to two independent judges with pre-defined criteria of inclusion and exclusion, this Study analyzed 25 cases integrally. In step 1, the protocol "Early Intervention Programs Characterization" (PIP) used to systematize information about participants, methodological considerations, intervention characteristics, studied variables, results, limitations and future studies, whose results indicated a predominance of indirect PIPs (13/25) that worked with training and formation of mediators. The presence of children in the PIP varied between forms of individual participation and groups. The mediators of the mixed intervention studies, who participated in PIP, along with children, were mainly parents / guardians. The categories of limitations and / or risks for development: Prevention, Risk and Disability, with a higher incidence of studies in category of Risks. Only one research used an equal control group design and follow-up evaluation was presented in three studies. Ten programs concurred with traditional paradigm and new paradigm, only one study presented characteristics of New Paradigm and the Family-Centered Model. The contexts in which interventions carried out were residences, kindergartens and university. Indirect interventions had a longer duration when compared to direct interventions. The target behaviors / abilities of intervention related to child development and parental and professional training. The results mostly evaluated as positive regardless of intervention type performed. Only three studies indicated non-effective results. 14 studies indicated limitations regarding both research design / procedure and intervention program. Questions raised for future research on methodology, such as longitudinal studies, extension of intervention, extension of sample searched and higher frequency of evaluations. Family demands related to parental / caregiver adherence to intervention programs, parents / child bonding and family / school relationship, and in professional context, knowledge about health surveillance and development surveillance was highlighted. In step 2, the protocol "Evaluation of Early Intervention Programs" (adapted from Mendes, 2010) used to analyze the programs within the community, family, child and intervention program, whose results indicated that community level, 14 studies did not indicate referral procedures, used voluntary or convenience samples. The eligibility criteria for PIPs quite diverse; 18 studies did not mention screening procedures for participation in program; information to families generally provided at beginning of program and it is also possible to inform that IPPs more directed to interests of researchers than to real needs of population. At the family level it can be verified that host interview and presentation the PIP were more frequent than actions that involved planning of support to families. At children's level, studies focused on social life and child autonomy. At PIP level, they showed more frequently performance of a single professional, without specific training; with activity plans that presented some information gaps such as: objectives, materials, teaching and registration procedures; few revisions in intervention proposals observed, with main concern in effectiveness of programs, whose evaluations based on non-standardized instruments. In the Step 1 results indicated that there was indirect predominance of PIPs (13/25) that worked with training, mediator development. The presence of children in PIP varied between individual forms participation and groups. Mediators of mixed intervention Studies, who participated in PIP, along with the children, were mainly the parents / guardians. Limitations and / or risks for development had been categorized: Prevention, Risk and Disability, with a higher incidence of studies in the category of Risks. Just one research used control group design and follow-up assessment presented by three Studies. Ten programs concomitantly met traditional paradigm and new paradigm, just one study presented characteristics of New Paradigm and the Family-Centered Model. The interventions carried out in residences, kindergartens and university. Indirect interventions had a longer duration when compared to direct interventions. The target behaviors / skills of intervention related to child development and parental and professional development. Independent of type of intervention performed, the results mostly evaluated as positive. Only three research indicated non-effective results. 14 studies indicated relative limitations to research design / procedure and intervention program. For future research, questions relating to methodology was highlighted, such as longitudinal studies, extension of intervention, extension of sample surveyed, higher frequency of evaluations. In family context, demands referred to participation of parents / caregivers in intervention programs, parents / child bond and family / school relationship, and in professional scope, knowledge about surveillance of development and health / education integration highlighted. Step 2 results indicated that in 14 studies there were no referral procedures in community analyzes level whose samples were voluntary or convenience; diversified eligibility criteria for PIPs; 18 studies no mention screening procedures for participation in the program; information had been provided in beginning of program for family; it is possible inform that PIPs more directed to researchers interests than real needs of population. In family level, it can verify that foster interview and PIP presentation were more frequent than actions with planning of support to families. In children's level, the studies focused on social life and children's autonomy. In PIP level emphasized more frequently performance of single professional, without specific qualification; activity plans with some gaps information such as: objectives, materials, teaching and registration procedures; few revisions in intervention proposals were observed, with main concern in effectiveness of programs, whose evaluations were based on non-standardized instruments. Study B analyzed posteriori assessment of researchers responsible for proposing and executing the Early Intervention Programs, as well as their continuity after their conclusion. Ten researchers answered a questionnaire with following topics: validity period, institutional support, concomitance between closure of research and program, and assessment of program regarding objectives / focus of intervention, screening procedures and evaluation procedures, family participation, engaged professionals, child development and results obtained vs expected. The results had been indicated that programs lasted up to 12 months; six of them had financial support; closure of the programs occurred concurrently in eight of them; it were positively evaluated by their proponents; it presented questions to be improved regarding theoretical reference, organization and planning of actions to be developed. It can indicate that research involving early intervention presented are important initiatives to deal to early stimulation in children with different risk factors and / or disabilities and producing knowledge in Brazilian context.